Enhanced removal of organic pollutants from super heavy oil wastewater using specially modified lignite activated coke. Issue 6 (16th April 2020) - Tong, Kun; Ji, Guodong; Nie, Fan; Zhang, Mingdong; Ren, Wen; Xie, Shuixiang
Abstract : Lignite activated coke (LAC) has been modified in situ by adsorbing the biodegradation effluent of super heavy oil wastewater (SHOW) to extract organic pollutants from raw SHOW before biodegradation is investigated. Abstract : Lignite activated coke (LAC) has been modified in situ by adsorbing the biodegradation effluent of super heavy oil wastewater (SHOW) to extract organic pollutants from raw SHOW before biodegradation is investigated. Results showed that, in comparison with LAC, modified lignite activated coke (MLAC) exhibited a higher COD removal amount and adsorption capacity with the increase of dosage. The modification process also contributed to a dramatic COD decrease in the final effluent of SHOW from 128.9 mg L −1 to below 50 mg L −1 . Particularly, characterization methods, GC-MS, FTIR, XPS and Boehm titration, were performed to investigate the relationship between the modification and the treatment performance. Results indicated that some basic substances were extracted from the biodegradation effluent by LAC during the modification process. Thus the alkali-nitrogen base abundant MLAC could remove larger acidic fractions from the raw SHOW during the adsorption process, leading to a higher adsorption capacity for MLAC. Furthermore, this clean and low cost in situ modification method also provides more reliable disposal effects for SHOW.